Essential strategies for efficient low–tar biomass gasification: in-bed intensification and interactive two–stage reactions - Chao Wang; Xinyu Wang; Zhennan Han; Mengjuan Zhang; Lianfeng Zhu; Xin Jia; Ping An; Dingrong Bai; Fang Wang; Guoqing Guan; Guangwen Xu (Resources Chemicals and Materials, 2025)
Gasification is a highly effective technology for converting biomass into fuel gas or syngas. While various gasifiers have been commercialized for fuel gas production, mitigating tar formation in gasifiers remains challenging. This review is devoted to summarizing the general strategies adopted in various gasifiers to reduce tar formation for high-efficiency clean gasification. For single-bed and staged-gasification processes, their low-tar strategies are typically different. In the single-bed processes, the low-tar strategies involve in-bed intensification achieved by controlling flow directions of gas and particles inside the gasifier. During the gasification, these two components often have different temperatures to facilitate thermochemical interactions between them. Meanwhile, the two-stage gasifiers are generally designed to decouple pyrolysis, gasification and tar cracking reactions for maximizing the benefits (such as yield and efficiency) realized from the interactions among these reactions. In addition to minimizing tar formation, the approach of reaction decoupling can also raise the calorific value of product gas, even without use of oxygen, and/or improve the adaptability of gasification technology to the feedstocks with various moisture contents and particle sizes. The reanalysis based on those essential low-tar strategies is expected to gain alternative insights into the reaction principles implicated in most advanced biomass gasification technologies.